2023
DOI: 10.3389/fpsyg.2023.1175675
|View full text |Cite
|
Sign up to set email alerts
|

Children’s total blindness as a risk factor for early parent-child relationships: preliminary findings from an Italian sample

Abstract: BackgroundVision provides crucial information for parent-child attunement that scaffolds social development from the first months of life. Congenital blindness might affect both parental wellbeing and children’s behavior during parent-child interaction. In this study, we compared families of young children with total versus partial blindness to understand the link between residual vision, parenting stress and perceived social support, and children’s behavior during parent-child interaction.MethodsParticipants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…We hypothesize that the high satisfaction demonstrated by parents in the questionnaires, is the result of the core approach of the RHF based on two pillars: a nurturing relational support and an individualized approach to help the parents achieve better health, well-being and quality of daily life for their children and themselves. Indeed, the Hollman early intervention program focuses on the health of the entire affective-relational family nucleus, giving importance to the needs, difficulties, strengths and weaknesses of the entire family, not just the child [37,39]. This hypothesis is in line with a recent study by Chen and Callahan Groves [51], which highlights the importance of emotional support for families of children with visual impairment in early intervention programs and services, showing how relationship-focused early intervention programs have led to positive developmental outcomes for children with disabilities [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the high satisfaction demonstrated by parents in the questionnaires, is the result of the core approach of the RHF based on two pillars: a nurturing relational support and an individualized approach to help the parents achieve better health, well-being and quality of daily life for their children and themselves. Indeed, the Hollman early intervention program focuses on the health of the entire affective-relational family nucleus, giving importance to the needs, difficulties, strengths and weaknesses of the entire family, not just the child [37,39]. This hypothesis is in line with a recent study by Chen and Callahan Groves [51], which highlights the importance of emotional support for families of children with visual impairment in early intervention programs and services, showing how relationship-focused early intervention programs have led to positive developmental outcomes for children with disabilities [52].…”
Section: Discussionmentioning
confidence: 99%
“…The conceptual roots of this program are the psychological theories on the affective-relational family development [32][33][34] and results of research on neuro-visual interplay during development occurring in children with vision loss in the first months of life [15,35]. These foundations, combined with the long-lasting experience of RHF professionals in their daily work with children with VI and with their families, allowed the implementation of this early intervention program with an individualized nurturing support to the family nucleus [36][37][38][39]. There are no studies that have evaluated how programs with these characteristics are viewed and whether they are appreciated by the families.…”
Section: Children's Earlymentioning
confidence: 99%
“…Additionally, Moore and McConachie [37] observed that mothers conversed less with 18-month-old children who had limited or no vision, offering fewer verbal labels and descriptions. Significantly, these challenges in interaction experienced by parents may further intensify their emotional strain, resulting in elevated levels of parenting stress, depression, and anxiety [38,39]. Consequently, this emotional burden could adversely impact the quality of stimulation provided to the child [40].…”
Section: Introductionmentioning
confidence: 99%